Association of coronary atherosclerosis with Stutzerimonas stutzeri strains (HaSa1, 2, 3, and 4) biofilm-forming bacteria - Yazan Ismail, Haqy; Abdul Salam Hamid Al-Sultan, Saba (Medicinski časopis, 2024)
Coronary atherosclerosis is called heart disease or atherosclerosis, which is one of the serious diseases whose rates began to increase during recent decades, especially in developing countries, including Iraq, specifically in the last twenty years, a rise in cases of coronary artery disease was observed. This study aimed to identify the involvement of Stutzerimonas stutzeri bacterial strains in coronary atherosclerosis. Methods: Samples were collected from patients undergoing Percutaneous Coronary Intervention (PCI); in Mosul Center for Cardiology and Cardiac Surgery between 9/10/2022 and 1/3/2023, samples were obtained using the fluid coming out of the balloon during angioplasty then putting the balloon sample in transport media (Tryptone Soya Broth), and advanced scientific methods were used to identify bacteria, such as a biochemical test, the Vitek-2 system, a Scanning Electron Microscope (SEM), and Molecular methods based on the 16S rRNA gene were used to corroborate at the species-level identification. Using BLAST software, the Nitrogen base sequences were located and compared to those of the NCBI. Results: The results showed that a new strains of bacteria stutzerimonas stutzeri were isolated for the first time in cases of coronary atherosclerosis, and it was registered in NCBI with the name ( Stutzerimonas stutzeri strain HaSa1, S. stutzeri strain HaSa2, S. stutzeri strain HaSa3, and S. stutzeri strain HaSa4).   The results also showed the ability of these bacterial strains to form a biofilm, which was diagnosed by a direct smear of the balloon sample, as well as from smears of isolated bacterial colonies stained with a gram stain, and also by photographing smears taken from the balloon sample by a Scanning Electron Microscope. In conclusion;  the isolation of new strains of S. stutzeri strains (HaSa1, 2, 3, and 4) from cases of atherosclerosis and its involvement in coronary atherosclerosis is demonstrated by its ability to form biofilms that promote chronic inflammatory responses.
Keywords: Stutzerimonas stutzeri; Percutaneous Coronary Intervention; Atherosclerosis; Angioplasty; Bacterial biofilm